HUMAN DEVELOPMENT INDEX AND AUDIT OPINION - Wahyudin Nor; Muhammad Hudaya; Rifqi Novriyandana; Dewi Lesmanawati; Melllani Yuliastina (JAFFA, 2018)
This study aims to investigate: the influence of human development indeks (HDI) and growth of HDI on auditor opinion and the difference between the level of HDI entities that get the predicate of qualified opinion or non qualified opinion. The data of this research comprise 1.482 out of 496 regency/cities governments in Indonesia during 2014-2016. The analysis techniques used are multiple regression and independent simple t test. The results of this study show that the human development indeks has influence on auditor opinion, the growth of human development indeks has influence on auditor opinion. The results of this study also found that the average performance of HDI between regency/ cities in Indonesia is different between of qualified opinion or non qualified opnion.